Afferent and efferent connections of the interpeduncular nucleus with special reference to circuits involving the habenula and raphe nuclei. Issue 10 (20th April 2017) - Lima, Leandro B.; Bueno, Debora; Leite, Fernanda; Souza, Stefani; Gonçalves, Luciano; Furigo, Isadora C.; Donato, Jose; Metzger, Martin
Abstract: The habenula is an epithalamic structure differentiated into two nuclear complexes, medial (MHb) and lateral habenula (LHb). Recently, MHb together with its primary target, the interpeduncular nucleus (IP), have been identified as major players in mediating the aversive effects of nicotine. However, structures downstream of the MHb‐IP axis, including the median (MnR) and caudal dorsal raphe nucleus (DRC), may contribute to the behavioral effects of nicotine. The afferent and efferent connections of the IP have hitherto not been systematically investigated with sensitive tracers. Thus, we placed injections of retrograde or anterograde tracers into different IP subdivisions or the MnR and additionally examined the transmitter phenotype of major IP and MnR afferents by combining retrograde tract tracing with immunofluorescence and in situ hybridization techniques. Besides receiving inputs from MHb and also LHb, we found that IP is reciprocally interconnected mainly with midline structures, including the MnR/DRC, nucleus incertus, supramammillary nucleus, septum, and laterodorsal tegmental nucleus. The bidirectional connections between IP and MnR proved to be primarily GABAergic. Regarding a possible topography of IP outputs, all IP subnuclei gave rise to descending projections, whereas major ascending projections, including focal projections to ventral hippocampus, ventrolateral septum, and LHb originated from the dorsocaudal IP. Our findings indicate that IP is closely associated to a distributed network of midline structures that modulate hippocampal theta activity and forms a node linking MHb and LHb with this network, and the hippocampus. Moreover, they support a cardinal role of GABAergic IP/MnR interconnections in the behavioral response to nicotine. Abstract : As revealed by tract tracing methods, both divisions of the habenula (MHb, LHb) project to the interpeduncular nucleus (IP), which is closely associated to a distributed network of structures that modulate hippocampal theta activity (blue letters) and forms a node linking MHb and LHb with this network, and the hippocampus.